Harnessing the power of clinician judgement. Identifying risk of deteriorating and dying in people with a haematological malignancy: A Delphi study. (19th November 2018) - Button, Elise; Gavin, Nicole C.; Chan, Raymond J.; Connell, Shirley; Butler, Jason; Yates, Patsy
Abstract: Aim: To provide expert consensus on the clinical indicators that signal a person with a haematological malignancy is at high risk of deteriorating and dying. Background: Identification of people who are at risk of deteriorating and dying is essential to facilitate patient autonomy, appropriate treatment decisions, and effective end‐of‐life care. Design: A three‐step modified Delphi approach. Methods: The study was conducted over 6 months (September 2015–March 2016) to gather opinion from an international panel of experts ( N  = 27) on the clinical indicators that signal a person with a haematological malignancy is at high risk of deteriorating and dying. The first round was informed by a systematic review of prognostic factors present in the final months of life for people with a haematological malignancy. Consensus was achieved if 70% of responses fell within two points on a seven‐point Likert‐type scale. Findings: Consensus was achieved on the following 11 clinical indicators: (a) advancing age; (b) declining performances status; (c) presence of co‐morbidities; (d) disease status; (e) persistent infections (bacterial and viral); (f) fungal infections; (g) severe graft versus host disease; (h) requiring high care; (i) signs of frailty; (j) treatment limitations; and (k) anorexia and/or weight loss. Consensus was also achieved on associated themes and statements for each indicator. Conclusion: The findings of this study indicate that subjective clinician‐assessed indicators that are contextually relevant to the nature of haematological malignancies are markers of risk. This study has provided valuable preliminary findings on the topic and will inform future research.